2018
DOI: 10.1016/j.resp.2018.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Exercise ventilatory irregularity can be quantified by approximate entropy to detect breathing pattern disorder

Abstract: Non-linear statistical interrogation of CPET-acquired ventilatory data has utility in the detection of BPD. A simple calculation of approximate entropy of ventilation, during an incremental cardiopulmonary exercise test, provides a quantitative method to detect BPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…(Elbehairy et al, 2016; Di Marco et al, 2017) These physiological considerations should be tempered with the observation that smokers have two to four times more panic-depression and anxiety disturbances compared to controls (Zvolensky et al, 2004; Moylan et al, 2012; Fadda et al, 2013). These abnormalities are associated with a chaotic breathing pattern and hyperventilation sindromes (Bokov et al, 2016; Bansal et al, 2018), and accordingly, contemporary models of fatigue point out to complex interactions between physiological activity and psychological state (Gruet, 2018). Hence, such complex “coordinated deadaptation”(Burtscher, 2013) in symptomatic smokers might lead to perceived fatigability (sensations about fatigue) and performance fatigability (incapacity of the neuromuscular system to meet the requirements of a given task) (Enoka and Duchateau, 2016).…”
Section: Respiratory Abnormalitiesmentioning
confidence: 99%
“…(Elbehairy et al, 2016; Di Marco et al, 2017) These physiological considerations should be tempered with the observation that smokers have two to four times more panic-depression and anxiety disturbances compared to controls (Zvolensky et al, 2004; Moylan et al, 2012; Fadda et al, 2013). These abnormalities are associated with a chaotic breathing pattern and hyperventilation sindromes (Bokov et al, 2016; Bansal et al, 2018), and accordingly, contemporary models of fatigue point out to complex interactions between physiological activity and psychological state (Gruet, 2018). Hence, such complex “coordinated deadaptation”(Burtscher, 2013) in symptomatic smokers might lead to perceived fatigability (sensations about fatigue) and performance fatigability (incapacity of the neuromuscular system to meet the requirements of a given task) (Enoka and Duchateau, 2016).…”
Section: Respiratory Abnormalitiesmentioning
confidence: 99%
“…In particular, CPET can detect chronic hyperventilation syndrome and ventilatory irregularity (corresponding to periodic deep sighing in the Boulding classification) as limitations to exercise capacity. 12,13 CPET studies of patients post-COVID have similarly shown a high prevalence of BPD, 14,15 but CPET is resource-intensive, limiting its use in the assessment of large numbers of patients in long COVID clinics.…”
Section: Discussionmentioning
confidence: 99%
“…Before the formal implementation of sports rehabilitation training, it was necessary to evaluate the symptoms, sports ability, quality of life, mental state and other aspects. Bansal’s team [ 67 ] evaluated the performance of 20 adults with disordered breathing on an incremental cardiopulmonary exercise test. It found that VO 2 max was lower than average and that patients more frequently cited dyspnea as the cause of their exercise limitations.…”
Section: Implications For Covid-19 Exercise Rehabilitation In Chinamentioning
confidence: 99%